O papel das emissoras educativas no Brasil em tempo de eleições - Burini, Débora (2011)
The concept of educational radio is present in the Brazilian Code of Broadcasting in 1963, valued by an Interministerial 1999.According to the Ministry of Communications, only 176 stations are considered educational universe of 3,000 existing radios in Brazil. In this context, the study proposes to establish a discussion on the educational experiences obtained from the radio, considering the Brazilian radio culture that favors concessions to trade groups and religious politicians. The challenge will be to move toward a program that combines educational content, entertainment, and thus ensures a common universe of communication skills enabling the adult radio listeners their actual interaction with the world around him. The methodology will work in the literature from texts on the subject, and the result of practical observations collected during visits to the broadcasters, programming and analysis.